The Characterization and Functional Properties of Euglena gracilis Paramylon Treated with Different Methods - Liwei Gao; Xinjie Zhao; Xiangzhong Zhao (International Journal of Analytical Chemistry)
Euglena gracilis paramylon (EGP) is a polymeric polysaccharide composed of linear β-1,3 glucan. The water insolubility of EGP severely limits its application. This work aimed to improve the functional characteristics of EGP by hydrogen peroxide (H2O2) degradation and carboxymethylated modification. The results showed that the crystallinity of EGP degraded by H2O2 and carboxymethylated modification decreased by 14% and 46%, and the thermal degradation temperature was significantly descending in a crystallinity-dependent manner. In addition, the results showed that H2O2 degradation and carboxymethylation significantly improved the adsorption capacity of EGP for oil, dyes, and metal ions, and their water solubility increased by 9% and 85%. This result will provide a valuable theoretical basis for the development and utilization of EGP.